ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR SISWA PADA KEMAMPUAN MEMBACA PERMULAAN KELAS 1 MIS BIDAYATUL HIDAYAH 3 DENA - Julfa Wardina; Muhammad Noer Fadlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify and analyze in depth the factors causing difficulties in learning to read at the beginning of first grade at MIS Bidayatul Hidayah 3 Denai, as well as to describe the efforts of teachers in overcoming these difficulties in order to improve the basic literacy skills of students. This study was motivated by the low level of reading skills among most students, as seen from initial observations where some students are not yet familiar with letters, are still in the spelling stage, and are unable to read with proper intonation and comprehension. The method used in this study is qualitative descriptive with a case study approach, which allows the researcher to examine contextually and in depth the symptoms and causes of reading difficulties. Data collection was conducted through direct observation, interviews with class teachers and parents, questionnaires, and documentation. The research subjects included 22 first-grade students, class teachers, and parents. The results showed that only 50% of students could read fluently, 23% were still sounding out words, and 27% could not read at all. The main findings indicated that reading difficulties are caused by internal factors such as lack of concentration, low motivation, weak reading interest, difficulty recognizing letters and spelling, as well as psychological factors such as low self-confidence. Additionally, external factors such as insufficient parental guidance at home, an unsupportive environment, and the use of inappropriate teaching methods also contribute to the low reading ability of students. Efforts made by teachers include dividing students into groups based on reading ability, providing special guidance, and applying global and syllable methods to help students gradually recognize letters, syllables, and words. This study concludes that improving early reading skills requires synergy between effective learning approaches, home environment support, and special attention from teachers to create a enjoyable and meaningful reading learning process for students from an early age.